ANALISIS REKRUTMEN POLITIK PARTAI GOLKAR JAWA TENGAH DALAM PEMILIHAN UMUM LEGISLATIF 2014 - DESKA APRILIANI KUMALASARI; SUSILO UTOMO; YUWANTO . (Journal of Politic and Government Studies, 2016)
ABSTRACTChange in political officer recruitment system of indirect election system makes political space becoming more competitive. In the context of political parliament recruitment there are some symptoms that are not conducive for the process of democratic development. First, the proportional electoral system has perpetuated the dominance of oligarchs in the recruitment process. Second, the recruitment process does not take place in an open and participatory way. Third, the recruitment process does not built a good relationship between political parties and civil society. Fourth, the electoral process and the recruitment process works in the context of a less educated and critical “floating mass”. These symptoms indicate the complicated problems in political recruitment towards a democratic political order in parliament mainly occur in the recruitment of candidates at the local level. These symptoms are attracting authors to conduct a study focusing on the recruitment of candidates of the Golkar Party in the Central Java Provincial Parliament from 2014 to 2019 period.The method of this thesis using qualitative research methods. The location of this research is located in the office of Central Java Golkar Party DPD. The informants in this research is the chairman of the Central Java Golkar Party DPD, administrators Central Java DPD Golkar Party and Golkar Party Candidates of DPRD Central Java Province. The results showed that the recruitment of the Golkar party has been run according to Surat Keputusan DPP Partai Golkar Nomor. KEP-227/DPP/Golkar/1/2013. In the assessment process of legislative candidates there is an element of subjectivity because there are no clear parameters related to standard size ratings.Therefore, the researchers suggest that the Golkar Party has a detailed  standard for legislative candidates political recruitment and more transparent in setting those candidates in order to improve the the quality of the candidates themselves. Key words: Golkar Party, Legislative Election 2014, Political Recruitment.